Handbook of Multimedia for Digital Entertainment and Arts 2009
DOI: 10.1007/978-0-387-89024-1_25
|View full text |Cite
|
Sign up to set email alerts
|

Information Technology and Art: Concepts and State of the Practice

Abstract: The intersection of information technology (IT) and art involves people from different disciplines with varying interests creating a milieu of interdisciplinary collaborations. In this context we explore the intersection of IT and art to understand different entities that are involved in the intersection. We do this by reviewing literature and reflecting and comparing our experiences from participation in five art projects. The objective is to develop a knowledge base at this interdisciplinary domain based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…As stated by Ahmed et al, that the interaction between information technology and communication (ICT) and art is increasing trend. Science, technology and technology have been connected since the 60's, when scientists, artists and inventors started to cooperate and use electronic instruments to create art [6]. Then Shanken suggested that In 1960 Marshall, predicted the idea that the era of "machine-age" technology was next to close, and the electronic media were creating a new way to perform art [7].…”
Section: Introductionmentioning
confidence: 99%
“…As stated by Ahmed et al, that the interaction between information technology and communication (ICT) and art is increasing trend. Science, technology and technology have been connected since the 60's, when scientists, artists and inventors started to cooperate and use electronic instruments to create art [6]. Then Shanken suggested that In 1960 Marshall, predicted the idea that the era of "machine-age" technology was next to close, and the electronic media were creating a new way to perform art [7].…”
Section: Introductionmentioning
confidence: 99%
“…The cast of players includes designers, robotics and software engineers, researchers and theorists, but it might also incorporate digital photographers, illustrators, 3D model makers, musical composers, performers and more. The scope of this intersection is well known: Nowadays software, electronics, mathematics, robotic technology, genetic art, algorithmic art, led installations, and artificial intelligence in union with music, dance, sculpture and painting expression are used to involve the audience as part of an interactive dialogue with technology (Ahmed et al, 2009). …”
mentioning
confidence: 99%